Encroached and enslaved: alienation of tribal lands and its dynamics - Viegas, Philip (New Delhi, 1991)
In the past few decades there has been a gradual weaning away of the tribals from the forests and from slash-and-burn cultivation in particular, which is now being replaced by settled cultivation. Tribal culture and economy, in addition to being intimately linked to forests, have also a close relationship to land. In the wake of these changes in their culture and economy, the tribals are faced with a whole spectrum of problems, land alienation being a major one among them. Further, in the context of rapid industrialisation, increased communication and the developmental model adopted by the country, the tribals, who have been physically displaced and culturally uprooted, are in constant conflict with the local bureaucracy and the landed class. A whole series of legislations have been promulgated by the Central and State Governments to protect the rights of the tribals over their lands. Many of these legislations have, however, inbuilt loopholes that have been very judiciously manipulated by the non tribals to concentrate land in their hands. This study, conducted in the tribal districts of Orissa, tries to take a deep look at the extent and causes of land loss. In a limited way, using the participatory action reflection-action approach, it attempts to probe into the processes and dynamics of the transfer of tribal land to non-tribals.
Keywords: Tribes